A new species of genus Thrips (Thysanoptera, Thripinae) from flowers in Peninsular Malaysia - Ng, Y. F.; Eow, L. X.; Mound, L. A. (Zootaxa, 2010)
Thrips is the largest genus in the Thysanoptera subfamily Thripinae, with 280 described species (Mound & Ng, 2009; Mound, 2010). Of these, 91 species are recorded from the Oriental and Pacific Regions (Palmer, 1992), and an identification key is available to the 23 species known from Peninsular Malaysia (Mound & Azidah, 2009). In the latter paper, the authors described one new species and recorded seven species as new records for the area, and these totals suggest that many more species are likely to occur here.